Cytosolic Ca(2+) Buffers - Schwaller, Beat (Cold Spring Harbor Laboratory Press, 2010)
“Ca(2+) buffers,” a class of cytosolic Ca(2+)-binding proteins, act as modulators of short-lived intracellular Ca(2+) signals; they affect both the temporal and spatial aspects of these transient increases in [Ca(2+)](i). Examples of Ca(2+) buffers include parvalbumins (α and β isoforms), calbindin-D9k, calbindin-D28k, and calretinin. Besides their proven Ca(2+) buffer function, some might additionally have Ca(2+) sensor functions. Ca(2+) buffers have to be viewed as one of the components implicated in the precise regulation of Ca(2+) signaling and Ca(2+) homeostasis. Each cell is equipped with proteins, including Ca(2+) channels, transporters, and pumps that, together with the Ca(2+) buffers, shape the intracellular Ca(2+) signals. All of these molecules are not only functionally coupled, but their expression is likely to be regulated in a Ca(2+)-dependent manner to maintain normal Ca(2+) signaling, even in the absence or malfunctioning of one of the components.